The Effect of NPK Based Sensors on Hydroponic Growth of Caisim Plants (Brassica Chinensis var. Parachinensis) - Oktaviani, Mutia; Fevria, Resti; Vauzia, Vauzia; Razak, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This study aims to make hydroponic plant cultivation the right alternative to overcome land limitations without the need for soil media. This study aims to determine the impact of using NPK-based sensors on the development of Caisim plants (Brassica Chinensis Var. Parachinensis) in a hydroponic system. The research design used a Completely Randomized Design (CRD) with two treatments, namely hydroponics with and without the help of IoT-based NPK sensors. Parameters include plant height, number and area of leaves, fresh weight, and dry weight. Data were analyzed using an unpaired T test at a significance level of 5%. The results show that the use of NPK sensors has a significant effect on most growth indicators, except for dry weight. The application of this sensor has been shown to increase the efficiency of nutrient absorption needed by plants. Therefore, this technology is worthy of being a modern solution in hydroponic cultivation to optimize production results efficiently.